Cashless Payment: Pengaruh Pendapatan, Diskon dan Cashback Terhadap Perilaku Konsumsi Islam Mahasiswa Lulusan Pesantren di Surabaya - Kamilatus Salsabila; Rachma Indrarini (El-Mal: Jurnal Kajian Ekonomi & Bisnis Islam, 2026)
This study aims to analyze the effect of income, discounts, and cashback on the Islamic consumption behavior of pesantren graduate students who use cashless payment systems in Surabaya. The background of this research arises from the growing use of digital payment methods, which may influence students’ consumption patterns. The study employs a quan-titative method with an explanatory research approach and purposive sampling technique involving 179 pesantren graduate respondents. Data were analyzed using Structural Equation Modeling (SEM) based on Partial Least Squares (PLS) with SmartPLS software. The results reveal that income and discounts have a positive and significant effect on Islamic consumption behavior, while cashback has no significant effect. These findings indicate that pesantren graduates maintain prudence and simplicity in financial transactions, particularly regarding cashback forms that are non-cashable and potentially contain elements of gharar (uncertainty). Overall, this study highlights the importance of designing digital promotions that comply with Islamic principles of transparency, fairness, and halal transactions in today’s cashless era.